Correlates of functional ankle instability in children and adolescents with Charcot-Marie-Tooth disease. Issue 1 (December 2015) - Rose, Kristy; Hiller, Claire; Mandarakas, Melissa; Raymond, Jacqueline; Refshauge, Kathryn; Burns, Joshua
Abstract Background Functional ankle instability (FAI) is commonly reported by children and adolescents with Charcot-Marie-Tooth disease (CMT), however, , the specific variables associated with FAI remain unknown. An improved understanding of these variables may suggest interventions to improve ankle stability and possibly prevent the long-term complications associated with ankle instability in this population. The aim of this study was to therefore investigate the relationship between FAI and other functional, structural, anthropometric and demographic characteristics in a cross sectional sample of children and adolescents with CMT. Methods Thirty children and adolescents with CMT aged 7–18 years were recruited from the Peripheral Neuropathy Clinics of a large tertiary paediatric hospital. Measures of FAI were obtained using the Cumberland Ankle Instability Tool (CAIT). Demographic and anthropometric data was also collected. Other variables collected included foot structure (Foot Posture Index), ankle range of motion (weight bearing lunge) and functional parameters (balance, timed motor function and falls). Descriptive statistics were calculated to characterise the participants. Pearson's correlation coefficients were calculated to investigate the correlates of right and left FAI and demographic (age), anthropometric (height, weight, BMI), foot/ankle (foot structure and ankle flexibility) and functional parameters (balance task, timed motor function and falls frequency). Point biserial correlation was employed to correlate gender with right and left FAI. Results All but one study participant (n  = 29) reported moderate to severe bilateral FAI with females reporting significantly greater ankle instability than males. FAI was significantly associated with cavus foot structure (r  = .69, P  < .001), female gender (r  = −.47, P  < .001) and impaired balance (r  = .50, P  < .001). Conclusions This study confirms FAI is common in children and adolescents with CMT. An examination of the correlates of FAI suggests interventions, which target balance, and normalise foot structure should be explored to evaluate whether they might help to improve ankle stability in this population.